Comparison of compressive strength in mud bricks with shred tires and concrete particles as sustainable materials - Niroumand, Hamed (Faculty of Civil Engineering, 2010)
Mud bricks consist of clay, water and different materials. Comparing mud bricks to concrete blocks, an evolution in reducing the cost and also in increasing the compressive strength, can be made. A weakness in mud block was shown during the experiments in the absence of additional materials. In consequence, a number of testing took place in mud bricks with different additional materials consisting of shred tires and particles waste concrete. Concrete particles are recycling materials as solid waste that is exported by concrete. To make the mud bricks, in this research different materials were used and concrete particles and shred tires were added in two layers in test boxes. This paper presents the role of different materials in mud brick strength that came as a result of our survey to their effect. The materials used are cheap one because we took them from solid waste and only a little part of them is used in the automotive industry. In this paper has been shown the change in compressive strength under additives materials in mud bricks. As a conclusion performances of mud bricks with shred tires were better than concrete particles.